Hadith #272 - Sunan al-Nasa'i - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
âThe Messenger of Allah (ï·º) said: âGive me the mat from the Masjid.'â She said: âI am menstruating.â The Messenger of Allah (ï·º) said: âYour menstruation is not in you hand.â
Grade:

Hadith #383 - Sunan al-Nasa'i - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Muhammad bin al-Muthna - al-Zaman ÙØÙØ¯ Ø¨Ù Ø§ÙÙØ«ÙÙ Ø£Ø¨Ù ÙÙØ³Ù - Ø§ÙØ²ÙÙ; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
âWhile the Messenger of Allah (ï·º) was in the Masjid, he said: âO âAishah, hand me the garment.â She said: âI am not praying.â He said: âIt is not in your hand.â So she gave it to him.â
Grade:

Hadith #630 - Sunan al-Nasa'i - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Ya'qub bin Ibrahim bin Sa'd ÙØ¹ÙÙØ¨ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
âAt the time of the Messenger of Allah (S.A.W) the phrases of the Adhan were said twice and the phrases of the Iqamah were said once, except that you should say: âQad Qamatis-Salah, Qad Qamatis-Salah (prayer is about to begin, prayer is about to begin).'â
Grade:

Hadith #945 - Sunan al-Nasa'i - Abdur Rahman bin Ibrahim Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ - Ø¯ØÙÙ; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Marwan bin Mua'wiya al-Fazari ÙØ±ÙØ§Ù Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙÙØ²Ø§Ø±Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
The Prophet (ï·º) said: âIt is not right for any one of you to say: âI have forgotten such and such a verse.â Rather, he has been caused to forget. Study the Qurâan, for it escapes from the heart of man faster than a camel escapes from its fetter. â
Grade:

Hadith #2034 - Sunan al-Nasa'i - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Muhammad bin 'Ubaid al-Tanafasi ÙØÙØ¯ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø£ÙÙØ© Ø§ÙØ·ÙØ§ÙØ³Ù; Qutayba bin Sa'id bin Jamil ÙØªÙØ¨Ø© Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù Ø¬ÙÙÙ; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
âThe Messenger of Allah forbade plastering over graves.â
Grade:

Hadith #3234 - Sunan al-Nasa'i - Abdur Rahman bin Ibrahim Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ - Ø¯ØÙÙ; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Marwan bin Mua'wiya al-Fazari ÙØ±ÙØ§Ù Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙÙØ²Ø§Ø±Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
It was narrated from âAmr bin Shuâaib, from his father, from his grandfather, that Marthad bin Abi Marthad Al-Ghanawi âa strong man who used to take the prisoners from Makkah to Al-Madinahâ said: âI arranged with a man to bring him (from Makkah to Al-Madinah). There was a prostitute in Makkah who was called âAnaq, and she was his friend. She came out and saw my shadow on the wall, and said: âWho is this? Marthad? Welcome, O Marthad, come tonight and stay at our place.â I said: â
Grade:

Hadith #3246 - Sunan al-Nasa'i - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Ali bin Hashim bin al-Burayd Ø¹ÙÙ Ø¨Ù ÙØ§Ø´Ù Ø¨Ù Ø§ÙØ¨Ø±ÙØ¯; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
It was narrated from Abu Hurairah that the Prophet said: âNone of you should propose marriage to a woman when someone else has already proposed to her.â
Grade:

Hadith #3247 - Sunan al-Nasa'i - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Sufyan bin Saâid Ath-Thawri Ø³ÙÙØ§Ù Ø§ÙØ«ÙØ±Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan al-Nasa'i)
âNone of you should propose marriage to a woman when someone else has already proposed to her, unless he marries (and he gives up the idea), or gives him permission.â
Grade:

Hadith #3233 - Sunan Abi Dawud - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Muhammad bin 'Ubaid al-Tanafasi ÙØÙØ¯ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø£ÙÙØ© Ø§ÙØ·ÙØ§ÙØ³Ù; Muhammad bin Abi Da'ud al-Bghdady ÙØÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø¯Ø§ÙØ¯; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Abi Dawud)
People with a bier passed by the Messenger of Allah (ï·º). They (the companions) spoke highly of him. He said: Paradise is certain for him. Then some people with another (bier) passed by him. They spoke very badly of him. He said: Hell is certain for him. He then said: Some of you are witness to others.
Grade: Sahih

Hadith #2289 - Jami' al-Tirmidhi - Abdur Rahman bin Muhammad al-Maharbi Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø²ÙØ§Ø¯ Ø§ÙÙØØ§Ø±Ø¨Ù; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Abu Karayb, Muhammad bin al-'Ala' ÙØÙØ¯ Ø¨Ù Ø§ÙØ¹ÙØ§Ø¡ - Ø£Ø¨Ù ÙØ±ÙØ¨; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Jami' al-Tirmidhi)
âI saw a black woman with unkempt hair going out of Al-Madinah, until she stood in Mabayaâah, and it is Al-Juhfah. So I interpreted that to be an epidemic in Al-Madinah that would spread to Al-Juhfah.â
Grade:

Hadith #3062 - Jami' al-Tirmidhi - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Jami' al-Tirmidhi)
ââEisa was taught his argument, Allah taught him regarding His saying: And when Allah will say: âO âEisa, son of Mariam! Did you say unto men âWorship me and my mother as two gods besides Allah?'â Abu Hurairah narrated from the Messenger of Allah (ï·º): âSo Allah taught him: âGlory be to You! It was not for me to say what I had no right (to say) (5:116).â The entire Ayah.
Grade:

Hadith #3406 - Jami' al-Tirmidhi - Abu Hurairah; Muhammad bin Bashar Bindar ÙØÙØ¯ Ø¨Ù Ø¨Ø´Ø§Ø± Ø¨ÙØ¯Ø§Ø±; Yahya bin Sa'id bin Farroukh al-Qatan ÙØÙÙ Ø¨Ù Ø³Ø¹ÙØ¯ Ø¨Ù ÙØ±ÙØ® Ø§ÙÙØ·Ø§Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Jami' al-Tirmidhi)
âI accompanied Shaddad bin Aws on a journey, so he said: âShould I not teach you what the Messenger of Allah used to teach us? That you say: âO Allah, I ask You for steadfastness in the affair and I ask You for determination upon guidance, and I ask You to make me grateful for Your favor, and excellence in worshiping You, and I ask You for a truthful tongue and a sound heart, and I seek refuge in You from the evil of what You know, and I ask You for the good of what You know, and I seek
Grade:

Hadith #1202 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ - Ø¯ØÙÙ; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Marwan bin Mua'wiya al-Fazari ÙØ±ÙØ§Ù Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙÙØ²Ø§Ø±Ù; Y'aqub bin Hmyd bin Kasb ÙØ¹ÙÙØ¨ Ø¨Ù ØÙÙØ¯ Ø¨Ù ÙØ§Ø³Ø¨ Ø§ÙÙØ¯ÙÙ; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
âWhen I die, then wash me with seven buckets from me well, the well of Ghars.â
Grade:

Hadith #1210 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ - Ø¯ØÙÙ; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Marwan bin Mua'wiya al-Fazari ÙØ±ÙØ§Ù Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙÙØ²Ø§Ø±Ù; Y'aqub bin Hmyd bin Kasb ÙØ¹ÙÙØ¨ Ø¨Ù ØÙÙØ¯ Ø¨Ù ÙØ§Ø³Ø¨ Ø§ÙÙØ¯ÙÙ; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
âIf one of the members of his family died, Hudhaifah would say: âDo not inform anyone of it, for I am afraid that that would be a public death announcement. I heard the Messenger of Allah (ï·º) with these two ears of mine forbidding making public death announcements.ââ
Grade:

Hadith #1511 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Sulaiman bin Hayan al-Azdi Ø³ÙÙÙØ§Ù Ø¨Ù ØÙØ§Ù Ø§ÙØ£Ø²Ø¯Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
âThe Messenger of Allah (ï·º) said: âThe person observing Iâtikaf may attend funerals and visit the sick.ââ
Grade:

Hadith #1636 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Muhammad bin 'Ubaid al-Tanafasi ÙØÙØ¯ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø£ÙÙØ© Ø§ÙØ·ÙØ§ÙØ³Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
that the Prophet Mohammad entered upon her, and he heard an effeminate man say to âAbdullah bin Abu Umayyah: âIf Allah enables you to conquer Taâif tommorrow, I will show you a woman who comes in on four (rolls of fat) and goes out on eight.â The Messenger of Allah said: âThrow them out of your houses.â
Grade:

Hadith #1639 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Muhammad bin 'Ubaid al-Tanafasi ÙØÙØ¯ Ø¨Ù Ø¹Ø¨ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø£ÙÙØ© Ø§ÙØ·ÙØ§ÙØ³Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
that the Prophet used to say, when offering congratulations of the occasion of marriage: âBarak Allahu lakum, wa barak âalaikum, wa jamaâa bainakuma fi khair (May Allah bless you and bestow blessings upon you, and bring you together in harmony).â
Grade:

Hadith #3299 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ - Ø¯ØÙÙ; Abu Bakr bin Abi Shayba Ø£Ø¨Ù Ø¨ÙØ± Ø¨Ù Ø£Ø¨Ù Ø´ÙØ¨Ø©; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Khlf bin Khlyfh Ø®ÙÙ Ø¨Ù Ø®ÙÙÙØ©; Marwan bin Mua'wiya al-Fazari ÙØ±ÙØ§Ù Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙÙØ²Ø§Ø±Ù; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
âI saw the Messenger of Allah (ï·º) marking sheep on their ears, and I saw him wearing a cloak around his wrist.â
Grade:

Hadith #3466 - Sunan Ibn Majah - Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Marwan bin Mua'wiya al-Fazari ÙØ±ÙØ§Ù Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙÙØ²Ø§Ø±Ù; Y'aqub bin Hmyd bin Kasb ÙØ¹ÙÙØ¨ Ø¨Ù ØÙÙØ¯ Ø¨Ù ÙØ§Ø³Ø¨ Ø§ÙÙØ¯ÙÙ; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
âZainab used to be called âBarrahâ (good), and it was said that she was praising herself. So the Messenger of Allah(ï·º) changed her name to Zainab.â
Grade:

Hadith #4117 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ - Ø¯ØÙÙ; Abu Hazim, Salma bin Dinar Ø³ÙÙØ© Ø¨Ù Ø¯ÙÙØ§Ø± Ø£Ø¨Ù ØØ§Ø²Ù Ø§ÙØ£Ø¹Ø±Ø¬; Abu Hurairah; Marwan bin Mua'wiya al-Fazari ÙØ±ÙØ§Ù Ø¨Ù ÙØ¹Ø§ÙÙØ© Ø§ÙÙØ²Ø§Ø±Ù; Swyd bin Sa'id Ø³ÙÙØ¯ Ø¨Ù Ø³Ø¹ÙØ¯; Y'aqub bin Hmyd bin Kasb ÙØ¹ÙÙØ¨ Ø¨Ù ØÙÙØ¯ Ø¨Ù ÙØ§Ø³Ø¨ Ø§ÙÙØ¯ÙÙ; Yazid bin Kysan al-Yshkry ÙØ²ÙØ¯ Ø¨Ù ÙÙØ³Ø§Ù Ø§ÙÙØ´ÙØ±Ù Ø£Ø¨Ù Ø¥Ø³ÙØ§Ø¹ÙÙ (Sunan Ibn Majah)
I heard âIrbad bin Sariyah say: âOne day, the Messenger of Allah (ï·º) stood up among us and delivered a deeply moving speech to us that melted our hearts and caused our eyes to overflow with tears. It was said to him: âO Messenger of Allah, you have delivered a speech of farewell, so enjoin something upon us.â He said: âI urge you to fear Allah, and to listen and obey, even if (your leader) is an Abyssinian slave. After I am gone, you will see great conflict. I urge you to adhere to m
Grade: